Explaining the money demand of non-financial corporations in the Euro area: A macro and a micro view - Carmen Martinez-Carrascal; Julian von Landesberger (European Central Bank (ECB), 2010)
This paper analyses euro area non-financial corporations (NFC) money demand, both from a macro and a microeconomic point of view. At a macro level, money holdings are modelled as a function of real gross added value, the price level, the long-term interest rate on bank lending to non-financial corporations, the own rate of return on M3 and the real capital stock of the NFC sector. The results indicate that NFCs' money holdings adjust quickly when deviations from their long-run level are registered, and that the large increase observed recently in NFCs' money holdings has been driven by changes in their fundamentals and hence they stand in line with their long-run equilibrium level. The disaggregated analysis also shows that cash holdings are linked to balance-sheet ratios (such as non-liquid short term assets, tangible assets or indebtedness) and other variables such as the firm' cash flow, its volatility or the size of the firm, which cannot be taken into account in the macro analysis. Likewise, results indicate that the main drivers of the increase in NFC cash holdings in the last years have been cyclical factors, captured by gross-added value and the cash-flow respectively. Variations in the opportunity cost of holding money, have also contributed to explain M3 developments but more modestly than at the end of the nineties, when its increase contributed negatively to cash accumulation.
Keywords: E41; C23; C32; D21; 330; cointegrated VARs; Money demand; panel estimation; Geldnachfrage; VAR-Modell; Panel; EU-Staaten